Distribution of ABO and RH Blood Groups in Western Region of Nepal - Mishra, Satyendra Kumar; Shakya, Ojeena; Pokhrel, Buddhi Raj; Poudel, Anuj; Srivastava, Manglesh Kumar (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTION Determination of ABO and Rh blood group types are clinically important for various purposes including blood transfusion. There is a wide regional, racial, and ethnic variability among these blood groups. We aim to determine the ABO and Rh blood group patterns in patients attending a tertiary care center of Western Nepal. MATERIAL AND METHODS This hospital-based cross-sectional study involved 600 patients visiting Universal College of Medical Sciences (UCMS), Bhairahawa undergoing blood group determination. The study was conducted for six months from 1st January to 30th June 2017. Ethical clearance for the study was taken prior to the study. Written and verbal consent were taken from each participant before the study. Blood group was determined using open slide test method and reverse grouping was performed via tube method. Finally, Rh-DU test was performed in Rh-negative samples to test for weak D antigen. RESULTS Among the ABO blood group, most common blood group was O (34.2%) followed by B (29.2%) and A (25.3%). Sub-group analysis showed only one A2 sub-group, the remaining being A1. Majority of the patients were Rh positive (95.8%). All the Rh negative patients tested negative for Du as well. The overall distribution pattern of combined ABO-Rh blood group was O+ > B+ > A+ > AB+ > O-> A- =B- > AB-. CONCLUSION In the current study, O positive was the most common blood group in Western Nepal followed by B positive, and A positive respectively. AB-negative was the rarest blood group. The study can provide insight for future hematological studies.